Me ajudem por favor é urgente
Anexos:
![](https://pt-static.z-dn.net/files/d5e/94352085ea09def235d745adc82faf5b.png)
Soluções para a tarefa
Respondido por
1
Resposta:
segue a resposta
Explicação passo-a-passo:
Basta substituir o valor de f em x
y = x + 1
a) f (1) = y = 1 + 1 = 2
b) f (2) = y = 2 + 1 = 3
c) f (3) = y = 3 + 1 = 4
d) f (-1) = y = -1 + 1 = 0
e) f (-2) = y = -2 + 1 = -1
f) f (-3) = y = -3 + 1 = -2
Perguntas interessantes
Física,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás